2017
DOI: 10.1016/j.ijscr.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Pylephlebitis and Crohn’s disease: A rare case of septic shock

Abstract: HighlightsWe describe a rare case of septic shock due to mesenteric pylephlebitis in a 47 years old man affected with Crohn’s disease.The occurrence of mesenteric pylephlebitis in Crohn’s disease is extremely rare, but to be considered in presence of a septic shock without clinical signs of peritonitis.Computed tomography scan confirmed the diagnosis and medical therapy led to a complete clinical remission of the mesenteric pylephlebitis.Optimizing pylephlebitis management, we performed an elective surgery aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The first case of pylephlebitis was reported in 1846 during an autopsy; however, the first case in a patient with IBD was not reported until 100 years later. 5 , 6 Pylephlebitis is commonly associated with diverticulitis, pancreatitis, cholangitis, peptic ulcer disease, liver abscess, and gastroenteritis. 6 Based on our literature review, less than 10 published cases have described pylephlebitis occurring in CD and only 5 cases are published in patients with UC (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first case of pylephlebitis was reported in 1846 during an autopsy; however, the first case in a patient with IBD was not reported until 100 years later. 5 , 6 Pylephlebitis is commonly associated with diverticulitis, pancreatitis, cholangitis, peptic ulcer disease, liver abscess, and gastroenteritis. 6 Based on our literature review, less than 10 published cases have described pylephlebitis occurring in CD and only 5 cases are published in patients with UC (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 6 Pylephlebitis is commonly associated with diverticulitis, pancreatitis, cholangitis, peptic ulcer disease, liver abscess, and gastroenteritis. 6 Based on our literature review, less than 10 published cases have described pylephlebitis occurring in CD and only 5 cases are published in patients with UC (Table 1 ). 2 , 7 These cases demonstrate a male predominance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anticoagulation is an area of controversy since no guidelines currently exist. According to the authors of one study there was a benefit observed with the combination of antibiotics and anticoagulation compared to antibiotics alone [8]. The benefits included a lower rate of mortality and recanalization failure.…”
Section: Discussionmentioning
confidence: 99%
“…The right portal vein, main portal vein, and superior mesenteric vein were each reported around 30% in one study [6]. More recent articles referencing inflammatory bowel disease are referring to Crohn’s disease and, to our knowledge, ulcerative colitis has not been mentioned since 1950 [2,8].…”
Section: Introductionmentioning
confidence: 99%